Stability study of organizational management structures - Bidnjak, Michael; Kompanets, Katarina (Technology audit and production reserves, 2016)
Comprehensive analysis of the formation of organizational management structures is given in the article. R. Norman model is chosen as the object of research, because it covers all operation systems of the companies. Today, holding of the companies in the changing environment of globalization leads to constant adaptation. This problem is solved by the formation of a new organizational and industrial structure, which is the basis for systems such as the integrity, structure and organization that it is necessary to companies. However, the research of work of the scientists in the field of formation of organizational structures incomplete takes into account the impact of the current conditions for development of companies, which require constant monitoring of external and internal conditions. Therefore it is necessary to use the modified methods for the formation of organizational structures. Research of R. Norman model led to the structurization of all components, key indicators are derived, which makes it possible to generate the algorithms of the optimal organizational structure.